A review of documentary film as authentic input in enhancing writing skills in ASL setting - Tg Abdul Rahman, Tg Ainul Farha; Chik, Abdul Rahman; Sahrir, Muhammad Sabri; Nordin, Mohd. Shukri (Penerbit Universiti Sultan Zainal Abidin (UniSZA), 2017)
The objectives of this paper are three folds: firstly, to highlight the studies which have used documentary film as authentic input in teaching second language skills, secondly to review the studies which have used documentary film in enhancing the second language writing skill, and lastly to offer ways to deal with documentary film in improving Arabic as a Second Language (ASL) writing skill. For this purpose, the paper analyses related literature review and previous studies in the field. The literature review shows the concern of second language practitioners as well as scholars in the field in using documentary film in the learning process. However, studies related to ASL are very scarce. There are four steps to be adopted for the purpose of linking documentary film input with enhancing writing skills output. The paper also highlights the strengths of documentary film as authentic input in language teaching as well as putting forth some technical advice and suggestions to improve the selection of teaching materials.